2024
DOI: 10.1002/mdc3.14020
|View full text |Cite
|
Sign up to set email alerts
|

RFC1 and FGF14 Repeat Expansions in Serbian Patients with Cerebellar Ataxia

Andona Milovanović,
Nataša Dragaševic‐Mišković,
Mirja Thomsen
et al.

Abstract: BackgroundThe newly discovered intronic repeat expansions in the genes encoding replication factor C subunit 1 (RFC1) and fibroblast growth factor 14 (FGF14) frequently cause late‐onset cerebellar ataxia.ObjectivesTo investigate the presence of RFC1 and FGF14 pathogenic repeat expansions in Serbian patients with adult‐onset cerebellar ataxia.MethodsThe study included 167 unrelated patients with sporadic or familial cerebellar ataxia. The RFC1 repeat expansion analysis was performed by duplex PCR and Sanger seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…Previous studies had shown that GAA-FGF14 ataxia may not be as common in the Japanese ataxia cohort (1.1%) [10]. In this study, GAA-FGF14 ataxia comprised only 0.3% (2/664) of our Chinese undiagnosed LOCA cohort, which was substantially lower than the French Canadian ataxia cohort (61%), European ataxia cohorts (5.4-51%), Indian ataxia cohort (10%), Brazilian ataxia cohorts (9%) and Australian ataxia cohorts (9.5%) [1,[3][4][5][6][7]. As we were preparing this report, we noticed that another research group found the low frequency (1.3%) of GAA-FGF14 ataxia in Chinese LOCA cohort [9].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Previous studies had shown that GAA-FGF14 ataxia may not be as common in the Japanese ataxia cohort (1.1%) [10]. In this study, GAA-FGF14 ataxia comprised only 0.3% (2/664) of our Chinese undiagnosed LOCA cohort, which was substantially lower than the French Canadian ataxia cohort (61%), European ataxia cohorts (5.4-51%), Indian ataxia cohort (10%), Brazilian ataxia cohorts (9%) and Australian ataxia cohorts (9.5%) [1,[3][4][5][6][7]. As we were preparing this report, we noticed that another research group found the low frequency (1.3%) of GAA-FGF14 ataxia in Chinese LOCA cohort [9].…”
Section: Discussioncontrasting
confidence: 51%
“…Expansion of intronic pure GAA repeats (expansion ≥250 triples) in FGF14 (GAA-FGF14) has been demonstrated to interfere with FGF14 transcription, resulting in GAA-FGF14 ataxia [1]. Although GAA-FGF14 ataxia was shown to be a common cause of SCA in French Canadian ataxia cohort (61%) [1] and European ataxia cohorts (5.4-51%) [3][4][5][6][7], it appeared relatively uncommon in Chinese (1.3%) and Japanese (1.1%) populations [8][9][10].…”
Section: Introductionmentioning
confidence: 99%